2011
DOI: 10.1155/2011/174689
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Increase in the Number of Oligodendrocytes Is Dysregulated in Schizophrenia and Mood Disorders

Abstract: The postnatal maturation of the human prefrontal cortex is associated with substantial increase of number of oligodendrocytes. Previously, we reported decreased numerical density of oligodendrocytes in the prefrontal cortex in schizophrenia and mood disorders. To gain further understanding of the role oligodendrocytes in pathogenesis of schizophrenia and mood disorders, we examined the effect of the age on the number of oligodendrocytes in the prefrontal cortex in schizophrenia, bipolar disorder, and major dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
43
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 96 publications
10
43
0
1
Order By: Relevance
“…This suggestion supports our previous data showing that the normal age-related increase in the number of oligodendrocytes in the prefrontal cortex was absent in schizophrenia 39 . These abnormalities may contribute to more profound abnormalities in the brain of patients with schizophrenia including abnormal expression of oligodendrocyte-and myelin-related genes, of genes that govern oligodendrocyte development and function, and of genes involved in the cell cycles.…”
Section: Discussionsupporting
confidence: 93%
“…This suggestion supports our previous data showing that the normal age-related increase in the number of oligodendrocytes in the prefrontal cortex was absent in schizophrenia 39 . These abnormalities may contribute to more profound abnormalities in the brain of patients with schizophrenia including abnormal expression of oligodendrocyte-and myelin-related genes, of genes that govern oligodendrocyte development and function, and of genes involved in the cell cycles.…”
Section: Discussionsupporting
confidence: 93%
“…Some investigators have found reduced white matter volume in depressed individuals (47), and recent investigations using diffusion tensor imaging (DTI) have identified lower fractional anisotropy (FA) in prefrontal regions, anterior cingulate, and temporal regions in depressed subjects (48). Severe depression and other neuropsychiatric disorders have also been associated with abnormal myelination (49,50) and reduced or abnormal oligodendrocytes (51), especially at older ages (52). …”
Section: Discussionmentioning
confidence: 99%
“…[63][64][65][66] In the latter, an age-related increase in number of mature oligodendrocytes normally observed in control subjects is absent in SZ patients. 67 Microarray analysis of patients' prefrontal and anterior cingulate cortices reveal a reduced expression of several genes related to myelin and oligodendrocytes [68][69][70] and an altered expression of genes coding for cell-cycle maintenance or arrest. 71 Altogether, these findings point to impaired oligodendrocyte maturation and myelination.…”
Section: Pvi/pnn Impairmentmentioning
confidence: 99%